(untitled) (Research, Society and Development, 2022)
Objective: To profile the occurrence accounts in the reporting forms of women who experienced drug-facilitated sexual assault between 2010 and 2019. Methodology: This is a quantitative, qualitative, cross-sectional research by means of secondary data collection from the epidemiological service of a hospital in Paraná State, Brazil. The sample comprised 342 reporting forms. Simple descriptive analysis and thematic content analysis on the brief occurrence report were used. Webqda® software was used for data organization. Results: The abusers made use of two ways to perpetrate the drug-facilitated sexual assault: they took advantage of voluntary drug or alcohol use by the women in 218 (66.06%) reports and they forced drug or alcohol use in 112 reports (33.93%). Conclusion: Coping with that violence depends on the implementation of preventive public policies, on the promotion of specialized services and qualified care, and on not blaming women for that abuse.